TINGKAT BERPIKIR KREATIF PESERTA DIDIK SMPN 3 RANAH PESISIR DALAM MENYELESAIKAN SOAL CERITA PADA MATERI ARITMATIKA SOSIAL KELAS VII - Rahma Mei Elvita; Yulia Yulia; Nita Putri Utami (Math Educa Journal, 2022)
Learners must be accustomed to thinking intelligently, carefully and logisstics which are indispensable in creative thinking. Able to solve more innovative problems without options with monotonous solutions. There is a purpose to describe the creative thinking level of students in solving math stories for clas VII social arithmetic material at SMP N 3 Ranah Pesisir in this study. Quantitative descriptive research is the type of research used. Class VII(1) students became the data source of this research. The data obtained are test of creative thinking skills and written interviews to students. The indicators of creative thinking according to Siswono are fluency, flexibility and novelty. Based on the results of the study, it was found that the creative of students in solving math story problems was classified as moderate with an average test results of 63,94. Students are at the very creative level as many as3 students (11,54%), creative as many as 16 students (61,54%), quite creative as many as 2 students (7,69%), and less creative 5 students (19,23%). The average provider per indicator, namely the fluency indicator with an average test result of 62,5 including the medium category, the flexibility indicator with an average test result of 64,42 including the medium category, the novelty indicator with an average test results of 64,9 included in the medium category.